Perhitungan Sederhana Nilai Tukar Riil Rupiah dan Keseimbangannya - Darinda, Dwika; Amir, Aprilianto (Business Perspective Journal, 2023)
For the public and private sectors, especially those dealing with the international world, monitoring exchange rate movements is very important. However, in the current conditions of volatility, uncertainty, complexity and ambiguity (VUCA), exchange rate projections become very challenging. Behavioral Equilibrium Exchange Rate (BEER) is a model used to estimate an exchange rate that is considered balanced based on fundamental factors. In connection with this, the author intends to inform you about BEER and its benefits. Therefore, this paper aims to estimate the balance of the real exchange rate (RER), so that exchange rate movements outside of equilibrium (misalignment) can be identified. The method used in this paper is the Error Correction Model (ECM). The author uses quarterly data with the aim of getting a long data series and more accurate estimation results. Meanwhile, the explanatory variables consist of productivity, interest rate differential, foreign reserves, terms of trade, and risk premium. From the estimation results, it is known that changes in productivity, interest rate differential and foreign exchange reserves have a significant positive effect on RER movements. The risk premium has a significant negative effect, while the terms of trade are not significant. It is hoped that the results of this simple analysis will provide additional insight for policy makers and economic practitioners in understanding the dynamics of the real rupiah exchange rate and efforts to maintain its stability. It is also hoped that this article will provide a strong basis for considering more effective policies in managing the rupiah exchange rate. Keywords: exchange rate, equilibrium, fundamental factor, flexibility